Cong Thuc Tich Phan

  • Published on
    18-Nov-2014

  • View
    767

  • Download
    0

Embed Size (px)

Transcript

<p>______________________________________________________________NG NHT MINH CONG THC TCH PHAN1)</p> <p>k .dx = k .x +C</p> <p>2)</p> <p>n x dx =</p> <p>x n +1 +C n +1</p> <p>3)</p> <p>x</p> <p>12</p> <p>dx = 1</p> <p>1 +C x</p> <p>4)</p> <p> x dx = ln x + C (ax + b) dxcos1 = 1 ln ax + b + C a</p> <p>1</p> <p>5) 7) 9) 11)</p> <p> (ax + b)sin</p> <p>n</p> <p>dx = </p> <p>1 + C ; 6) a ( n 1)( ax + b) n 1</p> <p>x.dx = cos x +C</p> <p>8) 10) 12)</p> <p>x.dx = sin x +C</p> <p> sin( ax + b)dx = a cos( ax + b) + C</p> <p>1</p> <p> cos( ax + b)dx = a sin( ax + b) + C</p> <p>1</p> <p> cos cosex</p> <p>12</p> <p>x</p> <p>dx = (1 +tg 2 x ).dx = tgx + C</p> <p> sin sine</p> <p>12</p> <p>x</p> <p>dx = (1 + cot g 2 x )dx = cot gx + C</p> <p>13) 15) 17) 19)</p> <p>2</p> <p>1 1 dx = tg ( ax + b) + C a ( ax + b)</p> <p>14) 16) 18) 20)</p> <p>2</p> <p>1 1 dx = cot g ( ax + b) + C a ( ax + b)dx = x +C e</p> <p>dx = e x +C</p> <p>x</p> <p>( ax +b ) dx = e x a dx =</p> <p>1 ( ax +b ) e +C a</p> <p>n (ax + b) .dx =</p> <p>ax +C ln a</p> <p>x</p> <p>2</p> <p>1 dx = arctgx + C +1</p> <p>1 (ax + b) n +1 . + C (n 1) a n +1</p> <p>21)</p> <p>x x2</p> <p>2</p> <p>1 1 x 1 dx = ln +C 2 x +1 1</p> <p>22)</p> <p>x1</p> <p>2</p> <p>1 1 x dx = arctg + C 2 a a +a</p> <p>23)</p> <p>1 1 x a dx = ln +C 2 2a x +a a</p> <p>24)</p> <p>1 x2 1 x 12</p> <p>dx = arcsin x + C</p> <p>25)</p> <p>1 a x2 2</p> <p>dx = arcsin</p> <p>x +C a</p> <p>26)</p> <p>dx = ln x + x 2 1 + C</p> <p>27)</p> <p>1 x a2 2</p> <p>dx = ln x + x 2 a 2 + C</p> <p>28)</p> <p>a 2 x 2 dx =</p> <p>x a2 x a2 x2 + arcsin + C 2 2 a</p> <p>29)</p> <p>x 2 a 2 dx =</p> <p>x a2 x2 a2 ln x + x 2 a 2 + C 2 2</p>